Flexural and morphology properties of Kenaf fibre reinforcement unsaturated polymer composite - Nurul Wahida Rusli; Mohamad Bashree Abu Bakar; Mohd Zharif Ahmad Thirmizir; Muhammad Azwadi Sulaiman; Mohamad Najmi Masri (Trans Tech Publications, 2017)
This study focus on the preparation of kenaf fibre reinforced unsaturated polyester composite through the compressing molding technique. The composite characterizations in flexural and morphological properties. Flexural test revealed that the incorporation of multiple layers of kenaf mat into unsaturated polymer composite (UPE) resulted in the increase of flexural strength. Nevertheless, the UPE alone still showed superior flexural strength since the presence of natural filler/fibre in polymer tends to reduce strength properties. The results proved that the UPE revealed the formation of microcracks. Thus, it has been noticed that the fiber fracture, fiber debondings and holes are some of the defects, which are observed due to the application of the load on the specimen.